2020
DOI: 10.1002/hbm.25310
|View full text |Cite
|
Sign up to set email alerts
|

Probing the role of the right inferior frontal gyrus during Pain‐Related empathy processing: Evidence from fMRI and TMS

Abstract: Recent studies have suggested that the right inferior frontal gyrus (rIFG) may be involved in pain‐related empathy. To verify the role of the rIFG, we performed a functional magnetic resonance imaging (fMRI) experiment to replicate previous research and further designed a noninvasive repetitive transcranial magnetic stimulation (rTMS) experiment to probe the causal role of the rIFG in pain‐related empathy processing. We assigned 74 volunteers (37 females) to three groups. Group 1 (n = 26) performed a task in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Although the current research has confirmed the modulation of INS function by acupuncture, the modulation of INS structure by acupuncture requires more investigation ( Jung et al, 2015 ; Dun et al, 2017 ; Guo et al, 2019 ; Duan et al, 2021 ). In addition, the modulation of the cingulate cortex (ACC, MCC) and IFG by acupuncture are associated with modulation of pain perception ( Fuchs et al, 2014 ) and empathic processing of pain ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the current research has confirmed the modulation of INS function by acupuncture, the modulation of INS structure by acupuncture requires more investigation ( Jung et al, 2015 ; Dun et al, 2017 ; Guo et al, 2019 ; Duan et al, 2021 ). In addition, the modulation of the cingulate cortex (ACC, MCC) and IFG by acupuncture are associated with modulation of pain perception ( Fuchs et al, 2014 ) and empathic processing of pain ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis showed higher activity toward ethnic minority (vs. majority) members in the right inferior frontal gyrus; and also higher activity toward Black (vs. non-Black) individuals in the left median cingulate cortex. The right inferior frontal gyrus is a region of the emotional empathy network (Schulte-Ruther et al, 2007;Jabbi and Keysers, 2008;Seitz et al, 2008;Perry et al, 2012;Peled-Avron et al, 2019;Li et al, 2021), and is also involved in executive functioning such as inhibitory control and attentional monitoring according to original studies (Aron et al, 2003(Aron et al, , 2014Hampshire et al, 2010;Gavazzi et al, 2017) and meta-analyses (Simmonds et al, 2008;Gavazzi et al, 2021). The left median cingulate cortex is a part of the mirror neuron system and involved in prosocial emotions (Amodio, 2014;Molenberghs and Louis, 2018).…”
Section: Neural Inter-group Bias In Ethnic Majority and Minority Membersmentioning
confidence: 99%
“…As a consequence, empathic concern can be linked to hostility in individuals who focus on potential threats to protect what they regard as precious or sacred. Interestingly, the neural basis of sacred value showed activation in the left inferior frontal gyrus, a region associated with rule retrieval, opposite to utilitarian cost–benefit reasoning [ 142 ], and this brain region is also the core structure of emotional empathy involved in the MNS [ 143 ]. Collectively, these findings suggest that affective empathy may be higher in some radicalized people defined as “devoted actors” (as opposed to rational actors), who are particularly prone to making costly and extreme sacrifices in the defense of sacred values [ 70 ].…”
Section: Consistency Between Empathy and Radical Beliefs And Behavior...mentioning
confidence: 99%